2020
DOI: 10.21873/cgp.20202
|View full text |Cite
|
Sign up to set email alerts
|

Association of Relative Leucocyte Telomere Length and Gene Single Nucleotide Polymorphisms (TERT, TRF1, TNKS2) in Laryngeal Squamous Cell Carcinoma

Abstract: Background/Aim: The study aimed to evaluate associations of relative leukocyte telomere length (LTL) and polymorphisms of telomere length-associated genes TERT (rs2736098), TERT-CLPTM1L (rs401681), TRF1 (rs1545827, rs10107605) and TNKS2 (rs10509637, rs10509639) in patients with laryngeal squamous cell carcinoma (LSCC). Materials and Methods: The study consisted of 300 patients with LSCC and 369 healthy control subjects. Genotyping and relative LTL measuring were carried out using qPCR. Results: Relative LTL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In recent years, TNKS2 has emerged as potentially useful chemical probe for several cancers. For example, Vaiciulis et al discovered that TNKS2 played crucial roles in laryngeal cancer [ 28 ]. Jumatovaite et al found the participation of TNKS2 in the progression of oral cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, TNKS2 has emerged as potentially useful chemical probe for several cancers. For example, Vaiciulis et al discovered that TNKS2 played crucial roles in laryngeal cancer [ 28 ]. Jumatovaite et al found the participation of TNKS2 in the progression of oral cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that telomeres are shorter in patients with laryngeal squamous cell carcinoma in the tumor differentiation grade 3 group than in the grade 1 and grade 2 groups. The grade 3 subgroup had the worst prognosis, with the highest mortality rate ( 59 ).…”
Section: Laryngeal Cancermentioning
confidence: 99%
“…Recently, rs8105767 variant within ZNF208 gene has attracted much attention in a genome-wide association study related to its relevance to telomere length ( Alves-Paiva et al, 2019 ). This variant was reported to be related to the risk of glioma and soft tissue sarcoma in a genome-wide association study related to its relevance to telomere length ( Vaiciulis et al, 2020 ; Gabriel et al, 2009 ). Nevertheless, this SNP was not associated with reduced telomere length in squamous cell carcinoma of the head and neck in a Chinese Han population ( Thomas et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The attention has been increasingly focused on investigations of telomeres and telomere length regulating genes, due to their importance in aging and development of chronic diseases and malignant tumors. Paulius Vaiciulis et al have found the association of relative leucocyte telomere length and gene single nucleotide polymorphisms (TERT, TRF1, and TNKS2) in LC ( Vaiciulis et al, 2020 ). However, the correlation between the gene mutations of telomere length–associated gene ZNF208 and LC remains uncertain.…”
Section: Introductionmentioning
confidence: 99%